Forecasting Imports with Information from Abroad - Christian Grimme; Robert Lehmann; Marvin Noeller (Center for Economic Studies and ifo Institute (CESifo), 2018)
Globalization has led to huge increases in import volumes, but the literature on import forecasting is still in its infancy. We introduce the first leading indicator especially constructed for total import growth, the so-called Import Climate. It builds on the idea that the import demand of the domestic country should be reflected in the expected export developments of its main trading partners. A foreign country's expected exports are, in turn, determined by business and consumer confidence in the countries it trades with and its price competitiveness. In a pseudo out-of-sample, real-time forecasting experiment, the Import Climate outperforms standard business cycle indicators at short horizons for France, Germany, Italy, and the United States for the first release of import data. For Spain and the United Kingdom, our leading indicator works particularly well with the latest vintage of import data.
Keywords: F01; F10; F17; 330; import climate; import forecasting; survey data; price competitiveness